Craniofacial Shape of Arfak People Based on Geometric Morphometric Features - Kawulur, Elda Irma Jeanne Joice; Suryobroto, Bambang; Budiarti, Sri; Hartana, Alex (UI Scholars Hub, 2018)
Face and cranial (craniofacial) shape is highly specific to the individual; therefore, craniofacial shape is often used to identify individuals and to analyze variability in the human population. Previous studies, consisting only of verbal descriptions, suggested that the cranial shape of the Papuan people was highly variable. Despite their usefulness, verbal descriptions cannot fully demonstrate common and local variation in cranial shape. They also cannot be used to extractthe general trend of variation or to group face shapes based on their similarity. Here we attempt to apply geometric analysis, a method of shape analysis, to measure facial anatomical structural landmarks of Papuan people. The craniofacial shape of Papuan people was constructed from those of Arfak people based on 16 anatomic landmarks on the lateral side. Arfak is one of the traditional Papuan tribes in Manokwari, West Papua Province. Our result showed great variation in craniofacial shapes among the Arfak. The nose, chin, and mandible differed significantly, whereas other parts of the face were relatively stable and showed small variations. These differences reflected variations in the facial growth rate. The high level of diversity thus indicates that some parts of the face have higher plasticity in their growth pattern than others.